Peran Pengasuh Panti Asuhan dalam Meningkatkan Kemandirian Anak Asuh di Panti Asuhan St. Lucy Medan Tuntungan - Putri Gea Maba Rizky; Jubaidah Hasibuan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines the role of caregivers in increasing children's independence at St. Lucy Orphanage using a qualitative approach with observation, interviews, and documentation. Four main roles of caregivers were found: mentor, motivator, role model, and coach. Caregivers apply a holistic and adaptive approach to build children's discipline, responsibility, self-confidence, and life skills. Although effective, the influence of the external environment and the diversity of children's characters need to be considered. These findings are supported by Bandura's social learning theory and Erikson's psychosocial theory. The study recommends ongoing training for caregivers and the development of an integrated coaching program. Longitudinal research is recommended for long-term evaluation.